Pertanggungjawaban Pidana Bagi Pelaku Pembegalan - Girsang, Hotlarisda; Senandi, Winna Amelia (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to analyze, explain and determine the act of robbery and the criminal responsibility imposed on the perpetrator. The type of research used is normative juridical which examines sources of primary legal materials consisting of statutory regulations, then secondary legal materials consisting of literature related to research, in the form of legal journals, written works, scholarly doctrines and various references. can be linked to research, then supported by tertiary legal material sources related to the issues raised in this research. The results of this research reveal that the act of robbery meets the requirements as a criminal act which is categorized as an act of robbery with violence as regulated in Article 365 of the Criminal Code and the criminal liability imposed on the perpetrator will be studied based on the elements of the article in Article 365 of the Criminal Code by looking at the form of the act and the consequences it causes.